Comparative Analysis of ARIMA and GARCH Methods to Predict Stock Prices - Atin Nuryatin (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
Investment has a very important role in economic growth, when investors invest, GDP tends to rise when investment falls, so GDP also tends to decline. Investors must be vigilant in investing in banking companies. One of the ways to predict stock prices with technical analysis is by using the ARIMA and GARCH methods. The purpose of this study is to determine whether the ARIMA and GARCH methods are accurate in predicting stock prices. The research method used in this research is descriptive and verification methods with a quantitative approach. Sources of data taken in this study are secondary data sources for the bank sub-sector found on the Indonesia Stock Exchange (IDX), namely the annual stock price reports for the years 2014, 2015, 2016, 2017, and 2018 as many as 39 companies. Processing data from this study using the ARIMA and GARCH methods with an evaluation of forecasting errors using the Root Mean Square Error (RMSE), Mean Absolute Error (MAE), or Mean Absolute Percentage Error (MAPE) analysis results using the E-View 9 program. shows that the ARIMA Method is accurate in predicting stock prices in 2015, 2016, and 2018. Meanwhile, the GARCH Method is accurate in predicting stock prices in 2014 and 2017.